Cidade, População em Situação de Rua e Estudos Organizacionais - Bruno Eduardo Freitas Honorato (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2016)
Is that possible to analyze street situation, in the city, adopting organizational analysis? This question is the base to a proposal of approximation between city studies and organizational studies, to try to push the boundaries of what is taken as organization and, this way, what can be object of organiza- tional analysis. We presume that once city is, by definition, “habited”, to observe it adequately, we need organizational analysis beyond public administration and urbanism, considering they who live in the city, once they determinate what it is, in fact. Starting from a model-city, subordinated to eco- nomic interests, and because of that, it needs to be “clean” to be immediately consumed, and about management role in promotion of global city, we discuss Michel de Certeau’s contributions about practiced cities and possible microfreedoms in popular appropriation of urban. Main conclusions suggest that city is a locus to organizational studies by excellence, once its multiples aspects are also possible parts of organizational analysis. Urban social dynamics allows multiple confronts, like order versus subversion ones, what exposes several possibilities do understand organizationally the city.